Mitigation of rain attenuation in equatorial region for MEASAT-2 and MEASAT-3 using orbital diversity - Agil, Halid (2012)
Rain is the main contributor towards signal attenuation for satellites operating above 3 GHz, and its effect becomes significant at 10 GHz and above. This causes satellite signal to experience degradation, and to some extent, signal cut-off. A tropical area such as Malaysia faces heavy rainfall throughout the year, and thus the satellite’s signal attenuation would occur frequently. This effect is undesirable for satellite services such as those provided by MEASAT satellites, as clients and customers demand for uninterrupted transmissions. Orbital diversity (OD) is seen to be a viable method to mitigate rain attenuation. It employs multiple satellites transmitting identical signal streams toward a mutual ground station. Although orbital diversity has been studied with great interest in regions such as Europe, there is little information of OD research in tropical regions, particularly in Malaysia. Therefore, this thesis proposed an analysis of an OD system in Malaysian climate using MEASAT satellites. An OD simulation model has been setup using parameters from MEASAT-2,MEASAT-3, and MEASAT Satellite Control Centre in Pulau Langkawi. It involved a rain attenuation prediction for each satellite, based on the ITU-R recommended rain attenuation model, signal gain prediction, and diversity gain prediction. The simulation model has been programmed in MATLAB environment. The results are obtained in numerical figures and graphs. The performance of the OD system is dependent upon the operating frequency and the satellite’s elevation angle. The simulation has shown that rain attenuation increases exponentially with the increase of frequency. Therefore, the signal gain decreases in an inverse exponential manner, particularly for individual signals of MEASAT-2 and MEASAT-3. Using signal combination, an OD signal can achieve a signal boost of up to 2.3 times the individual signal gain. With this significant finding, the OD is proposed to mitigate rain attenuation in Malaysia.